Deposition of Phase-pure Cr2AlC Coating by DC Magnetron Sputtering and Post Annealing Using Cr-Al-C Targets with Controlled Elemental Composition but Different Phase Compositions. Issue 3 (March 2018) - Li, Yueming; Zhao, Guorui; Qian, Yuhai; Xu, Jingjun; Li, Meishuan
Abstract: Polycrystalline Cr2 AlC coatings were prepared on M38G superalloy using a two-step method consisting of magnetron sputtering from Cr-Al-C composite targets at room temperature and subsequent annealing at 620 °C. Particularly, various targets synthesized by hot pressing mixture of Cr, Al, and C powders at 650–1000 °C were used. It was found that regardless of the phase compositions and density of the composite targets, when the molar ratio of Cr:Al:C in the starting materials was 2:1:1, phase-pure crystalline Cr2 AlC coatings were prepared by magnetron sputtering and post crystallization. The Cr2 AlC coatings were dense and crack-free and had a duplex structure. The adhesion strength of the coating deposited on M38G superalloy from the 800 °C hot-pressed target and then annealed at 620 °C for 20 h in Ar exceeded 82 ± 6 MPa, while its hardness was 12 ± 3 GPa.